Teachers' Perception of Using a Context-Based Approach in Mathematics Instruction - Roka, Jasbir; Khanal, Bishnu (Mangal Research Journal, 2024)
This study aims to investigate teachers' perceptions of the context-based approach (CBA) in mathematics at secondary-level schools. It employed an exploratory qualitative research design, utilizing semi-structured interviews with five purposively selected mathematics teachers from community-based secondary schools in Birendranagar Municipality, Surkhet District, Nepal. The collected data were analyzed using thematic analysis. The findings revealed that teachers perceived the CBA as effective and beneficial for teaching mathematics at the secondary level. Additionally, they demonstrated a theoretical awareness of its principles and applications. However, the study highlighted that teachers were not applying the CBA sufficiently in classroom instruction, indicating a gap between their conceptual understanding and the practical implementation of the approach in mathematics teaching. Based on these findings, the study strongly recommends the design and implementation of the Context-Based Instruction (CBI) approach to enhance academic outcomes in mathematics at the school level in Nepal.